Structural Design of the High Voltage Transmission Line Tower Climbing Robots - Zhang Dandan (Jixie chuandong)
Focusing on the fault and the maintain of the tower structure in the high voltage transmission lines,the high voltage tower climbing robot is designed,the robot carries many sensors and two cameras in the front and the end,thus,the robot could achieve to grab different types of angle iron in multi-angle.The model is established by using Solidworks,and the kinematics analysis and simulation of the tower climbing robot is established in the Solidworks.Because of the climbing and grab structure of the robot is important,the statics analysis of the key position are carried out in the ANSYS Workbench.